STRATEGI PEDAGANG KAKI LIMA TERHADAP PERDA NO. 3 TAHUN 2000 (Studi Kasus di Lapangan Puputan Margarana Denpasar) - Sri Rahayu, Maria (PIRAMIDA, 2012)
Vendors or in Indonesian, PKL (Pedagang Kaki Lima) is one of modes incity transformation which is not separable from economic system of the city.Vendors are one of businesses which have high spirit of entrepreneurship but thissector often encounters difficulties. Policy of the government tends to marginalizethis sector. Rukmana (2005) said that vendors fenoment in economic system ofthe city isn’t the unsucess social group of the suburb economic system. The socialgroup is not the component of suburb economic which is to be responsibility ofcity development.This location of this research is the area of Lapangan Puputan Margaranathat is to be called Lapangan Renon, Denpasar. The location choised is based onsome reasons, such as 1) the area is prohibited for vendors and 2) the area is notfar from the center of city goverment.From the research, it could be concluded that vendors who remain in thearea does not mean that they oppose the government by violating the regulationbut that act (strategy) is done by rational factors. They have to do that becausethey have to fight for life, either it is economically, socially and culturally.
Keywords: strategy, government, vendors (PKL)